ANALISIS PENGARUH FAKTOR GENDER DAN LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA MAHASISWA (Studi Pada Mahasiswa Program S1 Manajemen Fakultas Ekonomika dan Bisnis Universitas Diponegoro) - Yunilasari, Indah; Rahardjo, Rahardjo (Faculty of Economics and Business Diponegoro University, 2016)
This study aims to analyze the influence of Gender and Family Environment toward college student’s entrepreneurial interest. This study was conducted towards student of S1 Management Faculty of Economics and Business, Diponegoro University. The number of samples in this study is 91college students of S1 FEB management UNDIP the force from 2012 to 2015. The technique to testing data is multiple linear regression analysis.The results of this study indicate that the gender variable has no significant effect on the college student’s entrepreneurial interest. While the family environment positively and significantly affect the college student’s entrepreneurial interest. Gender and family environment variables simultaneously influence college student entrepreneurial interest by 10.5% and 89.5% were influenced by other factors.